Effect of sowing date on quality seed production of sweet pepper in Bangladesh (Progressive Agriculture, 2017)
A field experiment was conducted to study the effect of sowing date on quality seed production of sweet pepper at the research farm of Seed Technology Division, Bangladesh Agricultural Research Institute, Gazipur, during 2011-2012. The aim of this study was to find out the optimum sowing date for quality seed production of sweet pepper. The treatments were 4 four sowing dates viz. 15 October, 30 October, 15 November and 30 November. Seeds were sown in seed bed for 1st sowing on 30 September, for 2nd sowing on 15 October, for 3rd sowing on 30 October and for 4th sowing on 15 November. The experiment was laid out in randomized complete block design (RCB) with three replications. The highest individual fruit weight, 1000 seed weight was obtained from the October 15 sowing date in the year of 2011-2012 and it was significantly different from all other dates of sowing. Maximum seed yield (86.2 kg ha-1) was recorded in 2nd sowing date (15 October) followed by 3rd sowing date (30 October) treatment while the lowest was found from 4th sowing date (15 November) (30.72, kg ha-1). Maximum seed quality as measured by moisture content, dry weight, vigour index and germination percentage were obtained at different sowing date. Maximum seed weight (mass maturity) was achieved at 1st sowing when average seed moisture contents were 5% and 4%, respectively. For high seed quality, sweet pepper is better sowing time at 2nd sowing time (15 October) which could be regarded as the point of physiological maturity.Progressive Agriculture 28 (3): 216-221, 2017